24. Season seven [videorecording (DVD)] - Turner, Brad; Todd, Tony, 1952-; Sutherland, Kiefer, 1966-; Jones, Cherry, 1956-; Bernard, Carlos; Wersching, Annie, 1977-; Rajskub, Mary Lynn, 1971-; Garofalo, Janeane; Voight, Jon, 1938- (Twentieth Century Fox Home Entertainment, 2009)
Set in Washington, D.C. for the first time. The CTU has been dismantled and Jack is on trial for all his 'misconduct' at the department. Jack's day takes an unexpected turn when someone threatens the government and his expertise is needed again.